Housing affordability in Malaysia : An overview at districts level. - Mohamed Osman, Mariana (2019)
The government is highly concerned with the issue of housing affordability. Affordable housing is important as housing is a pressing necessity, especially for B40 income households in Malaysia. Studies have shown that Malaysia is presently struggling with the issue of housing affordability whereby its median multiple for housing affordability in the year 2014 was 5.1. In some states such as Perak, Kelantan, Terengganu and Selangor, soaring house prices have made it almost impossible for the low income and even the middle-income group to buy a home. This study compares household income against housing prices in each district within states in Malaysia. The data were collected from primary sources in the form of focus group discussions, roundtable discussion and interviews with the main stakeholders in Malaysia coupled with secondary data and content analysis to identify housing affordability in Malaysia. Due to data limitation, this study adopted the median multiple approach in determining housing affordability for all districts in Malaysia. Data on annual income was sourced from the Department of Statistics Malaysia’s Household Income Survey for the years 2012, 2014 and 2016 from which the Housing Affordability Index was generated. Based on the Index, housing affordability fluctuates with certain states such as Melaka which have most of their district at affordable level. The increase in the median multiple of the districts can be attributed to the increase in house prices which was disproportionate to the increase in the income of the population. The findings of this study can be used to aid the state government in their endeavours to provide quality affordable housing policies and programmes for all.